Determinants of Double Burden of Malnutrition Among School Children and Adolescents in Urban Dhaka: A Multi-Level Analyses - Tariqujjaman, Md.; Sheikh, Sifat Parveen; Smith, George; Hasan, A. M. Rumayan; Khatun, Fatema; Kabir, Ashraful; Rashid, Md. Harunor; Rasheed, Sabrina (Frontiers in Public Health, 2022)
Background: Bangladesh faces a double burden of malnutrition, with a rising prevalence of overweight and obesity among children parallel to existing undernutrition. Objective: The current study was designed to assess the determinants of double burden of malnutrition among urban school children from Dhaka, Bangladesh. Methods: A cross-sectional survey was conducted among 2690 students from 14 schools in Dhaka city from January to June 2018. Anthropometric measurements were taken during school hours, and self-administered questionnaires were sent to the parents. We performed multi-level multiple logistic regression analyses to assess the determinants of underweight, overweight, and obesity. Findings: The prevalence of overweight (33%) and obesity (23%) was highest among children and adolescents from high tuition schools but the prevalence of underweight (4%) was lowest compared to those from low (underweight 19%, overweight 17% and obesity 6%) and medium (underweight 18%, overweight 15% and obesity 6%) tuition schools. Children from high-tuition schools had higher odds of being overweight/ obese (AOR: 2.92; 95% CI: 1.90, 4.49). Parental NCDs and overweight were negatively associated with underweight but positively associated with overweight and obesity among children. Lack of physical activity inside schools was positively associated (AOR: 1.26; 95% CI: 1.02, 1.55) with overweight and obesity among school children. Conclusion: Our results point to opportunities in and outside schools to address the rising prevalence of underweight, overweight, and obesity among urban school children.